Un quehacer cotidiano: Proyecto de mediación de la exposición hacer en lo cotidiano - David Lanau; Eva Morales (Midas: Museus e Estudos Interdisciplinares)
This article intends to assess the terminology ‘mediation’ as well as its practice, through the experience that Invisible Pedagogies – a research and action arts education collective – developed for the exhibition “Everyday Doings” (hacer en lo cotidiano) between February and September 2013. At Invisible Pedagogies, we believe in multiple methodologies in enacting mediation and we want to introduce our own practices. Our main concern is to render the public visible as one of the agents involved in the cultural production process, understanding the act of mediation as the creation of a space for encounters, reflections, experiences and knowledge production generated between the works of art, the public, the curatorial discourse and the educators.